2022
DOI: 10.3389/fonc.2022.1019106
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of chemoresistance to first-line chemotherapy and its possible association with autophagy in high-risk neuroblastoma

Abstract: High-risk neuroblastoma (NB) is sensitive to chemotherapy but susceptible to chemoresistance. In this study, we aimed to analyze the incidence of chemoresistance in high-risk NB patients and to explore the role of autophagy in NB chemoresistance. We retrospectively analyzed the incidence of changing the chemotherapy regimen due to disease stabilization or disease progression during induction chemotherapy in high-risk NB patients, which was expressed as the chemoresistance rate. The autophagy levels were probed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…Our investigation illustrates that inhibiting miR-30a using an antagomir molecule increases the levels of ATG5 protein to activate LC3-II, which in turn reduces apoptosis and then promotes resistance to docetaxel in MDA-MB-231 cells. These findings are consistent with the results observed in other studies on chemotherapy-resistant cancer cells [20,36,37]. Furthermore, HIF-1α-induced activation of autophagy assumes a pivotal role in liver and bladder cancer cells [9,38].…”
Section: Discussionsupporting
confidence: 92%
“…Our investigation illustrates that inhibiting miR-30a using an antagomir molecule increases the levels of ATG5 protein to activate LC3-II, which in turn reduces apoptosis and then promotes resistance to docetaxel in MDA-MB-231 cells. These findings are consistent with the results observed in other studies on chemotherapy-resistant cancer cells [20,36,37]. Furthermore, HIF-1α-induced activation of autophagy assumes a pivotal role in liver and bladder cancer cells [9,38].…”
Section: Discussionsupporting
confidence: 92%
“…Cisplatin. CQ enhanced the sensitivity to CIS treatment in endometrial adenocarcinoma cells [35], thyroid cancer cell lines (TPC1, ACT1, and KTC1) [41], and SH-SY5Y cells [63]. In all of these cells, CQ effects were associated with the suppression of autophagy accompanied by increased LC3 and p62 expression.…”
Section: Chloroquine-and Platinum-based Anticancer Drugsmentioning
confidence: 97%
“…Inhibition of autophagy by hydroxychloroquine (HCQ) sensitizes NB cells to vincristine ( Belounis et al, 2016 ). Similarly, Chen et al (2022) reported that chemotherapeutic agents including cisplatin, cyclophosphamide, and etoposide combined with chloroquine (CQ) increased the chemotherapeutic sensitivity and cell apoptosis of high-risk NB cells. These facts indicated that autophagy is closely associated with chemoresistance and can be a potential target in the treatment of NB.…”
Section: Underlying Mechanisms Of Therapy Resistance In Nbmentioning
confidence: 98%